SURGICAL TREATMENT OF LARGE PERIAPICAL LESIONS USING MTA AS RETROGRADE RESTORATION - CLINICAL CASE - Dana Cosac; Cristian Niky Cumpătă; Ştefan Manea; Anna Maria Pangică (Amaltea Medical Publishing House, 2019)
Large apical lesions at the anterior teeth have a fairly high frequency. These require a treatment approach that ensures full biological healing and functional restoration of the tooth or teeth involved. A cystic apical lesion, which can not be cured by non-surgical endodontic treatment, will be treated with surgical intervention with retrograde filling, literature recommending the use of MTA as a retrograde filling material. This article presents a clinical case for the surgical management of a cystic lesion using MTA as a retrograde material. Surgical endodontics is a reliable treatment method for managing such cases that do not respond to conventional root canal treatment.